Engaging a Whole Child, School, and Community Lens in Positive Education to Advance Equity in Schools - Chafouleas, Sandra M.; Iovino, Emily A. (Frontiers in Psychology, 2021)
Recent decades of education policy, research, and practice have brought focus on a positive education approach as applied within tiered service delivery frameworks to meet diverse needs of varied intensities. Related, the science of implementation has begun to increase understanding of supports to strengthen use of a positive education approach within tiered service delivery frameworks. To date, the body of work has fostered important shifts in how problems are viewed and addressed using a positive lens, supporting more equitable opportunity in education. To realize the full potential, however, there is a need to integrate theory and science as embedded within a whole child, school, and community lens. We propose that positive education will advance equity when grounded in integrated theory and science across developmental systems theory, prevention science, ecological systems theory, and implementation science. We first provide a brief overview of schools as a context to serve as assets or risks to equity, followed by a discussion of theory and science using a whole child, whole school, and whole community lens. We end with directions for science and practice in advancing a positive education approach.